For each non-empty subset of integers { 1 , 2 ⋯ , n } , consider the reciprocal of the product of the elements. Let S n denote the sum of these products. For example, S 3 = 1 1 + 2 1 + 3 1 + 1 ⋅ 2 1 + 1 ⋅ 3 1 + 2 ⋅ 3 1 + 1 ⋅ 2 ⋅ 3 1 .
Find the sum of digits of S 2 0 1 3 .
This problem is shared by Jasper S .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Well done! This is a great example of a problem that can be naturally done by induction, and this solution is an excellent example of how such proofs can be written.
Well done!
Good solution! Never thought of it.
That's a cool solution.
I also did the same thing
i did'nt get you properly....cud u pls be a little more clear?
Log in to reply
Well they were talking about induction . In this method we prove that the given statement is true ∀ x ∈ Z + ⇒ S x = x .
We first put in x=1 i.e
S 1 = 1
Now, we assume in x = n i.e
S n = n
Now we prove that S n + 1 = n + 1
Hence now we can say that ∀ x ∈ Z + , S x = x
Therefore , S 2 0 1 3 = 2 0 1 3
Hence , Sum of digits = 6
Firstly, we will prove that S n = n . From the given sum, adding 1 to each side, we will have S n + 1 = ( 1 + 1 ) ( 1 + 2 1 ) ( 1 + 3 1 ) ( 1 + 4 1 ) . . . ( 1 + n 1 ) S n + 1 = 2 . 2 3 . 3 4 . . . n n + 1 S n + 1 = n + 1 S n = n So S 2 0 1 3 = 2 0 1 3 , and its sum digits is 6
Nicely done!
We begin by testing cases with small n . For n = 1 , S 1 = 1 1 = 1 . For n = 2 , S 2 = 1 1 + 2 1 + 1 ⋅ 2 1 = 1 . For n = 3 , S 3 = 1 1 + 2 1 + 3 1 + 1 ⋅ 2 1 + 1 ⋅ 3 1 + 2 ⋅ 3 1 + 1 ⋅ 2 ⋅ 3 1 = 3 . We thus conjecture that S n = n . We notice that S n − S n − 1 = n 1 + n S n − 1 . Through induction, we see that S n = S n − 1 + n 1 + n S n − 1 = ( n − 1 ) + n 1 + n n − 1 = n . We note that S 1 = 1 , so S 2 0 1 3 = 2 0 1 3 and its digit sum is 2 + 0 + 1 + 3 = 6 .
Well explained!
1 1 + 2 1 + 3 1 + 1 × 2 1 + 1 × 3 1 + 2 × 3 1 + 1 × 2 × 3 1
=( 1 1 + 2 1 + 3 1 + 1 × 2 1 + 1 × 3 1 + 2 × 3 1 + 1 × 2 × 3 1 +1)-1
=(1+ 1 1 )(1+ 2 1 )(1+ 3 1 )-1
= 1 2 × 2 3 × 3 4 -1
=4-1
=3
WLOG
Answer=2+0+1+3
I suspect that your proof is pretty much the same as Arika S.'s one. But "WLOG" is not appropriate here.
If we put S 2013 under a common denominator, the numerator becomes (1+1)(2+1)...(2013+1)-2013! and the denominator is 2013!. But then S 2013 = 2014!/2013! - 2013!/2013! = 2014-1=2013. It follows the answer is 2+0+1+3=6.
We can recursively determine the values of S n and regroup these to notice that S n = S n − 1 + n 1 S n − 1 + n 1 . For instance, S 3 = 1 1 + 2 1 + 1 ⋅ 2 1 + 3 1 ( 1 1 + 2 1 + 1 ⋅ 2 1 ) + 3 1 .
Assuming S n − 1 = n − 1 , this gives S n = n n + 1 ( n − 1 ) + n 1 = n n 2 = n and so, inductively, we notice S n = n . The sum of digits of 2 0 1 3 of course is 6.
Let A = 1 , 2 , 3 , . . , n and lets look at non-empty subsets of A. When n=1 They are ( 1 ) . The non-empty subsets of A when n=1 are also valid when n=2. The non-empty subsets when n=2 that are not in case n=1 can be obtained by adding 2 to every non-empty subset when n=1 and also adding ( 2 ) to the list. Hence the non-empty subsets of A when n=2 are ( 1 ) , ( 2 ) , ( 1 , 2 ) . Generally in case n the non-empty subsets of A are the non-empty subsets of A in case n-1, the non-empty subsets of A in case n-1 with n added to them and ( n ) .
Lets now look at the sum given in the problem. By the exercise above it can easily be found that S 2 = 1 1 + 1 × 2 1 + 2 1 . To find S 3 we use the procedure above and find that S 3 = 1 1 + 1 × 2 1 + 2 1 + 3 1 ( 1 1 + 1 × 2 1 + 2 1 ) + 3 1 = S 2 + 3 1 S 2 + 3 1 . Using this procedure we find that in general S n = S n − 1 + n 1 S n − 1 + n 1 (we "add" n to a subset by multiplying with n 1 ). Now we use induction to show that S n = n . It is trivial that S 1 = 1 so we assume for n ≥ 1 that S n = n . Then we have:
S n + 1 = S n + n + 1 1 S n + n + 1 1
= n + n + 1 1 n + n + 1 1 = n + n + 1 n + 1 = n + 1 .
Therefore for every n ≥ 1 , S n = n . So S 2 0 1 3 = 2 0 1 3 , hence the answer 2 + 0 + 1 + 3 = 6 .
Take 1 / ( n ! ) We get the following as the numerator
Summation of single terms + Summation of ( product of two ) terms + Summation of ( product of three ) terms + ..............+ Summation of ( product of n - 1 ) terms
Consider the numerator as a quadratic expression in x :
[ ( x + 1 )( x + 2 )( x + 3 )( x + 4 )................( x + n ) ] - n!
The above expression is valid for x = 1 : So putting x = 1
we get Numerator = ( n + 1 ) ! - n !
We had taken common n ! in the beginning ; so dividing the above with n !
We get Sn = [ ( n + 1 ) ! - n ! ] / ( n ! )
or Sn = n ...........
Answer is 2 + 0 + 1 + 3 = 6
S2013 is 2013.The question here is sum of digits of S2013 which is 6
/{S_{3}/}=3
Therefore, /{S_{2013}/}=2013
The sum of the digits is 2+0+1+3=6
6 is the answer
This is a good guess, but not a proof. Try to understand the Riley P.'s solution.
Problem Loading...
Note Loading...
Set Loading...
Looking at the first few cases, we note that S 1 = 1 , S 2 = 2 , S 3 = 3 .
So it remains to prove the case in general, (ie S 2 0 1 3 = 2 0 1 3 )
We show this by induction:
We take a base case of n = 1, S 1 = 1 is trivial.
Now suppose S n = n
Then note that S n + 1 contains all the fractions in S n , and to catch all the new subsets we add n + 1 1 S n
(Since the new subsets are just all the old ones with the addition of n+1)
We add a n + 1 1 to account for the set of just n+1, giving:
S n + 1 = S n + n + 1 S n + n + 1 1 = n + 1 , Q E D
So we now have that S 2 0 1 3 = 2 0 1 3 , which has sum of digits 6